Revitalizing science education: Unveiling the potential of 2D animations to enhance understanding and engagement - Rahim, Sarni Suhaila; Abdullah, Aini Amera; Parumo, Shahril; Khartini Jali, Suriati (Little Lion Scientific, 2024)
This research paper explores the transformative potential of 2D animations in revitalizing science education by enhancing understanding and engagement among learners. A comprehensive literature review examines previous studies on educational animations, emphasizing the cognitive impacts of visual aids on learning. The article presents an evaluation of 2D Animation for Science Secondary School Learning: Acid and Alkali. The developed application was produced to assist science students to understand the contents of the topic Acid and Alkali. An experiment was carried out to assess the effectiveness of the application as a learning tool for science students. There was a total of 32 respondents, including subject matter experts, multimedia experts and students. The findings of the current study showcased the positive impact on student engagement and learning outcomes. The results may assist in advocating for a paradigm shift in science education. The research underscores the need for innovative approaches that leverage the power of 2D animations to inspire and educate learners, thereby contributing to the ongoing revitalization of science education.